Strengthening Public Sector Talent Management through 360° Feedback: A Meritocratic Approach to Performance Evaluation - Widodo Putra Suharto; Heriyanto Heriyanto (Journal of Government Science Studies, 2025)
This study investigates the implementation of merit-based talent management through the MANTAP innovation in West Kalimantan Province, Indonesia, in response to the persistent limitations of the civil service performance appraisal system that has been criticized as top-down and lacking objectivity. The research aims to analyze how the integration of the 360° feedback mechanism strengthens the provincial merit system while addressing structural and cultural challenges in regional bureaucracy. A qualitative single case study approach was employed, focusing on the Regional Civil Service Agency (BKD) and two key Regional Apparatus Organizations (the Health Office and the Public Works Office). Data were collected between 2024 and 2025 through 12 purposively selected informants including structural officials, policy implementers, and civil servantsalongside document analysis, evaluation reports, and direct observation of the digital feedback process. Data were analyzed thematically using open and axial coding, following Braun and Clarke’s (2006) framework, with triangulation and member checking to ensure validity. The findings show that MANTAP enhances transparency, accountability, and fairness in civil servant competency assessments by involving multiple evaluators (superiors, peers, subordinates, and self). It also broadens opportunities for talent identification and merit-based promotions. However, challenges remain, including resistance from senior officials, hierarchical work culture, and limited digital literacy and infrastructure. The novelty of this study lies in demonstrating how a 360° feedback mechanism can be successfully applied in a provincial government with constrained digital infrastructure and entrenched seniority normscontexts that have received limited scholarly attention.